Penerapan Model Pembelajaran Problem Based Learning dengan Pendekatan Sains Teknologi Masyarakat untuk Meningkatkan Kualitas Pembelajaran Biologi Siswa Kelas XI.IPA 5 SMA Negeri 1 Karanganyar Tahun Pelajaran 2012/2013Penerapan Model Pembelajaran Problem Based Learning dengan Pendekatan Sains Teknologi Masyarakat untuk Meningkatkan Kualitas Pembelajaran Biologi Siswa Kelas XI.IPA 5 SMA Negeri 1 Karanganyar Tahun Pelajaran 2012/2013 - Kusumawardani, Kusumawardani; Sudarisman, Suciati; Indrowati, Meti (Universitas Sebelas Maret, 2013)
The purpose of this research was to improve quality of biology learning considered by teacher’s performance, utility of facilities in the classroom, classroom climate, student’s scientific attitude, and student motivation to learn in class XI.IPA 5 SMA Negeri 1 Karanganyar academic year 2012/2013. This research was a Classroom Action Research which performed in three cycles. Each cycle consisted of 4 phases; planning, action, observation, and reflection. The data was collected by questionnaire, observation, and interview. Data validation was used triangulation of methods and triangulation of observers. The obtained data were analyzed using descriptive technique. Result of the research showed that according triangulation the average percentage for teacher’s performance in pre cycle (63.96%), cycle I (90.21%), cycle II (95.83%) and cycle III (100%); classroom climate pre cycle (70.22%), cycle I (86.43%), cycle II (83.30%) and cycle III (84.65%); student’s scientific attitude pre cycle (69.31%), cycle I (76.20%), cycle II (77.61%) and cycle III (83.45%); and student motivation to learn pre cycle (67.01%), cycle I (70.33%), cycle II (73.97%) and cycle III (77.69%); utility of learning facilities in the classroom have been optimally. The results showed that the average percentage quality of biology learning aspect such as pre cycle (67.63%), cycle I (80.79%), cycle II (82.68%) and cycle III (86.45%). The quality of biology learning was increase 18.82% from pre cycle to cycle III. Cycles stopped in cycle III because the research target was achieved. The conclusion describes that the implementation of problem based learning with science technology society approach was able to improve the quality of biology learning considered by teacher’s performance, utility of facilities in the classroom, classroom climate, student’s scientific attitude, and student motivation to learn in class XI.IPA 5 at SMA Negeri 1 Karanganyar in academic year 2012/2013. Key Words: Problem Based Learning, Science Technology Society Approach, Quality of Biology Learning